A Comparative Study of Conventional and Statistically Active Corrosion Methods for Corrosion Growth Assessment of a 24-inch Gas Pipeline - Rinaldi, Rudi; Fatriansyah, Jaka Fajar (UI Scholars Hub, 2024)
Component failures in oil and gas pipelines can have fatal consequences, leading to operational downtimes and environmental damage. Knowledge of the corrosion growth rate is fundamental to pipeline integrity management, as it is essential for risk assessment and decisions related to asset management. This article aimed to compare two approaches for the corrosion growth estimation of the 24-inch offshore gas pipeline: the conventional method versus the Statistically Active Corrosion (SAC) method. This article is based on the in-line inspection (ILI) results of two consecutive assessments from 2020 to 2023 of the entire 73 km of the pipeline. The results show that the SAC method evaluates the corrosion activity on the pipeline with better accuracy and localization than the conventional method, highlighting 782 corrosion active joints in the 5,987 pipeline joints. The SAC method leads to much higher average and maximum corrosion growth rates while also being able to pinpoint active corrosion locations more accurately. Thus, the SAC method is an efficient and simple strategy to cope with corrosion assessment problems regarding pipeline integrity management. It enables the operators to prioritize their maintenance actions, improving pipeline safety.